The possibility of using Scots pine needles as biomonitor in determination of heavy metal accumulation - Alaqouri, Houriyah Ateeyah Alwizri; Genc, Cigdem Ozer; Aricak, Burak; Kuzmina, Nadezhda; Menshikov, Sergey; Cetin, Mehmet (Springer Science and Business Media LLC, 2020)
One of the biggest problems of modern world is the air pollution which causes the death of millions of people every year. The heavy metals included in the component of air pollution occupy an important position in human health since they could remain intact in nature for a long time and build bioaccumulation, and also some of them are toxic or carcinogenic even at some low concentrations. Even the heavy metals functioning as micronutrient element could create toxic effect for human beings at the high concentrations. For this reason, the determination of the heavy metal concentration has an important role in terms of the detection of risky regions and risky level. One of the primary sources of heavy metals is industrial plants where the heavy metal ores are processed. Those regions might have risks at high level in terms of particular heavy metals. Consequently, it is significant to find out in which level they influence the area around these plants and to what extent the heavy metal pollution is effective. In this study, Ba, Zn, Cd, K, and Na concentrations are determined by analyzing the samples which are taken from 1- and 2-year-old needles of Scots pines (Pinus sylvestris L.) growing in 1 km, 3 km, 10 km and 25 km distances around a processing and mining of magnesite ore in Russia. In the end of the study, it is concluded that generally, the concentrations of heavy metals subject to the study are increasing depending upon the distance, and this increase is quite apparent in some elements, and finally in many points, the concentrations determined in 2-year-old needles have higher levels than 1-year-old needles.
Keywords: Child, Preschool; Metals, Heavy; Humans; Infant; Soil Pollutants; Pinus sylvestris; Environmental Monitoring; Russia; 13. Climate action; 11. Sustainability; 3. Good health